Willingness of end users to pay for e-waste recycling - H.T.T. Nguyen; C.-H. Lee; R.-J. Hung (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: The sheer volume of electrical and electronic waste (e-waste) has presently been generated in Vietnam, posing a growing concern regarding its impact can have on the environment and human health. Therefore, the need for developing policies and regulations towards the environmentally sound management of e-waste is becoming crucial. Although the municipalities play an important role in e-waste recycling program, there does not appear to be any study involving residents’ perceptions on e-waste management. This paper aims to examine the influencing factors of end users’ willingness to pay and their payment preferences toward e-waste recycling.  METHODS: The logistic regression model was employed to analyze a qualified data set collected through a personal interview survey in Danang city, Vietnam. All analyses were conducted using Statistical Package for Social Sciences software (version 22.0).  FINDINGS: The results revealed that the end users’ willingness to participate in recycling programs, laws and regulations, inconvenience of recycling and past experience were four key determinants significantly contributing to the willingness to pay for recycling e-waste. With regards recycling payment methods, most of the participants (36%) were in favor of deposit and refund scheme, while pre-disposal fees and advanced recycling fees came in second and third place (25.8% and 21%, respectively), making monthly payment of recycling fees the least preferred (10.2%).  CONCLUSION: These findings may provide policy-makers with crucial information for better e-waste management policy development, which helps address the conflict between development and conservation, may be applicable in Vietnam and other countries as well.